1996
DOI: 10.1073/pnas.93.18.9630
|View full text |Cite
|
Sign up to set email alerts
|

In vitro binding of type 1-fimbriated Escherichia coli to uroplakins Ia and Ib: relation to urinary tract infections.

Abstract: Urinary tract infections, caused mainly by Escherichia coli, are among the most common infectious diseases. Most isolates of the uropathogenic E. coli can express type 1 and P fimbriae containing adhesins that recognize cell receptors. While P fimbriae recognize kidney glycolipid receptors and are involved in pyelonephritis, the urothelial receptors for type 1 fimbriae were not identifled. We show that type 1-fimbriated E. coli recognize uroplakins Ia and Ib, two major glycoproteins ofurothelial apical plaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
211
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(217 citation statements)
references
References 41 publications
4
211
0
2
Order By: Relevance
“…More recently, the antibacterial activity of diamond particles [36], [37] and [38] and their potential to interfere with biofilm formation [1] have been highlighted. The underlying anti-adhesive strategy proposed was based on the interfering with type 1 fimbriae-mediated mannose recognition events [39]. Such biofilm disrupting activity had not been observed previously for other glyco-nanoparticles (glyco-NPs) such as glycofullerenes, goldbased glyco-NPs or for other multivalent mannose-derived molecules [2] and [40].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the antibacterial activity of diamond particles [36], [37] and [38] and their potential to interfere with biofilm formation [1] have been highlighted. The underlying anti-adhesive strategy proposed was based on the interfering with type 1 fimbriae-mediated mannose recognition events [39]. Such biofilm disrupting activity had not been observed previously for other glyco-nanoparticles (glyco-NPs) such as glycofullerenes, goldbased glyco-NPs or for other multivalent mannose-derived molecules [2] and [40].…”
Section: Introductionmentioning
confidence: 99%
“…An inflammatory process occurs shortly after this binding process has been initiated. A number of studies have demonstrated that interactions between the Fim H adhesin and epithelial cells on the bladder's surface are essential for colonisation and www.intechopen.com infection of bladder epithelium with strains of uropathogenic E. coli (Sun 1996, Wu et al 1996. This specific 'adhesin-epithelial cell' binding process occurs when type 1 pili bind to uroplakin 1a (UP1a) and uroplakin 1b (UP1b) (Malaviya and Abraham 1998).…”
Section: Type 1 Pilimentioning
confidence: 99%
“…They are caused mainly by uropathogenic Escherichia coli (UPEC), which rely on several virulence factors to cause disease (2); type 1 pili (T1P) are perhaps the most important of these (3). T1P present a tip adhesin, FimH, that binds specifically to mannose, which is found on several glycosylated surface proteins, such as uroplakins and α1-and β3-integrins (4,5), in the mammalian bladder. Binding to mannosylated proteins initiates a cascade of events including UPEC invasion of host tissues (2), formation of intracellular structures (6), and activation of the host immune response (7).…”
mentioning
confidence: 99%